2023
DOI: 10.1302/2046-3758.122.bjr-2022-0391.r1
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid neutrophil extracellular traps could improve the diagnosis of periprosthetic joint infection

Abstract: Aims This study aimed to explore the diagnostic value of synovial fluid neutrophil extracellular traps (SF-NETs) in periprosthetic joint infection (PJI) diagnosis, and compare it with that of microbial culture, serum ESR and CRP, synovial white blood cell (WBC) count, and polymorphonuclear neutrophil percentage (PMN%). Methods In a single health centre, patients with suspected PJI were enrolled from January 2013 to December 2021. The inclusion criteria were: 1) patients who were suspected to have PJI; 2) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Recent research has shown that their involvement in the pathogenesis of PJI could take place through the formation of neutrophil extracellular traps (NETosis) ( Cai et al, 2023 ). NETosis reflects part of the innate immune response to pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that their involvement in the pathogenesis of PJI could take place through the formation of neutrophil extracellular traps (NETosis) ( Cai et al, 2023 ). NETosis reflects part of the innate immune response to pathogens.…”
Section: Discussionmentioning
confidence: 99%
“… 26 In terms of pathogen diagnosis, similar results were obtained in this study. Currently, with the development of metagenomic next-generation sequencing (mNGS), broad-range polymerase chain reaction (BR-PCR), and other molecular diagnostic methods, 27 , 28 the molecular detection results could be used as a supplement for the diagnosis of PJI in addition to microbial culture. We achieved good clinical outcomes through standardized revision procedures, which indicated that, regardless of the kind of spacer, standardized treatment for pathogenic bacteria, including multiple specimen collection procedures, thorough debridement, and the combined topical and systemic application of antibiotics, 29 is the key to long-term infection management.…”
Section: Discussionmentioning
confidence: 99%
“…[87][88][89][90] Use of neutrophil extracellular traps (NETs) as a synovial fluid biomarker has shown usefulness at effectively diagnosing PJI in culture-negative PJI, fungal PJI, and those on antibiotics with an area under the curve (AUC) between 0.95 and 0.99. 91 Calprotectin, a protein found in the cytoplasm of neutrophils, has high sensitivity and high specificity and may be useful as a ruleout test for PJI. 92 Cytokines and chemokines including chemokine (C-C motif) ligand 20 (CCL20), cytokine/chemokine regulator oncostatin M (OSM), a danger-associated molecular pattern known as extracellular newly identified receptor for advanced glycation endproducts binding protein (EN-RAGE), IL-8, and IL-6 are increased in sonicate fluid samples compared with aseptic revisions and are not differentially expressed based on infective species.…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…LE is an enzyme that is produced by activated neutrophils that can be detected by a colorimetric strip test and α‐defensin, an antimicrobial peptide secreted by neutrophils, can be detected by enzyme‐linked immunosorbent assay (ELISA) both with high sensitivity and specificity 87–90 . Use of neutrophil extracellular traps (NETs) as a synovial fluid biomarker has shown usefulness at effectively diagnosing PJI in culture‐negative PJI, fungal PJI, and those on antibiotics with an area under the curve (AUC) between 0.95 and 0.99 91 . Calprotectin, a protein found in the cytoplasm of neutrophils, has high sensitivity and high specificity and may be useful as a rule‐out test for PJI 92 …”
Section: Transcriptomics and Proteomics–biomarkersmentioning
confidence: 99%